A Review Of The Climate Change Funding Under The United Nations Framework Convention On Climate Change (unfccc) - With Reference To The Case Of Algeria - Abi, Khalida (University of eloued - جامعة الوادي, 2018)
The aim of this study is to give a review of the framework of multilateral climate funds which represent a funding mechanism under the United framework convention on climate change (UNFCCC), through its establishment, funding status and The World Bank's important role across the provision of financial intermediary services, as Trustee of the funds. as well as providing a set of agreed financial services that involve receiving, holding and investing contributed funds, and transferring them under the financial intermediary funds governing body. Moreover, we look to highlight the role of the multilateral climate change funds, to assist developing countries to combat climate change effects, through the promotion of its investments in the field of combating climate change effects, like renewable energies investments and to benefit from the funding of climate funds within UNFCCC. With reference to Algeria's current situation and the extent to which it benefited from funding in this framework.
مقال
Keywords: Climate change, The United Nations Framework Convention on Climate Change (UNFCCC), Multilateral climate funds, Adaptation fund, Global environment facility, Green climate fund, Algeria